Development Method of Village Consultative Body Post Head Village Election in Kalikayen Village, East Ungaran District - Qibtiyah, Mariyatul; Muafifah, Siti (Indonesian Journal of Advocacy and Legal Services, 2019)
Various conditions after the Head Village Election have a great impact to the development of village itself especially on Village Constulative Body structure. The article highight some problems: (1) What is urgency of Village Council developing method, post Head of Village Election in Kalikayen?; and (2) What is the method of Village Council Development, Post Head of Village Election in Kalikayen? Therefore, there is a method of developing Village Council Post Village Election in order to answer the challenges mentioned above. The purpose of this program is to find out the guidance carried out by the regional government of the Village Council, the Village Council to be able to carry out their duties properly, and submit proposals to the government to pay more attention to the implementation of village government. After the completion of this dedication, the Village Council now understands their duties and functions as well as its role in village development. In addition, the Village Council already has the knowledge and experience in drafting village regulations. Outcomes of our service programs include the publication of a village guidebook module that contains the optimization of the implementation of the Village Law, the management of village funds, the techniques for establishing regulations in the Village. The next output is the draft village regulations and the village head regulations, as well as the activity proposal form and problem priority of each backwoods.